Animus et conscientia – gnozeologiczne przesłanki Augustyńskiej aksjologii - Warchał, Robert (Humaniora. Czasopismo Internetowe, 2020)
It all points to the evidence that experience in the onto-gnoseological approach was defined by the thinker from Tagasty as a joint functioning of cognitive and intellectual acts, which is not without significance when it comes to the abovementioned relationship of axiology and gnoseology. The phenomenon of conscience demonstrates the true value of humanity, in which experience seen from onto-gnoseological point of view is a condition for the realization of good and love. It seems clear that the reflections of the Christian thinker convey an extremely complex introspection structure, in which we can capture several interpretations of internal conscience, such as experience that results from co-action of intellectual and volitional functions. For the Augustine, a man who wants to live in accordance with his nature, i.e. pursues happiness and wants to be truly authentic, must constitute a harmonious whole, whose basic elements, such as the psyche, the spiritual sphere (in the biblical sense) and the flesh, create a coherent system called a person. It is clear from Augustin’s ontology that human is good by nature, and hence if he sins, it is because he acts against his nature. This great philosopher strongly emphasizes that evil is a deviation and distortion of the creation and thus of the law established by God.